EFFECTS OF EXERCISE ON IMPROVING THE HEALTH OF CHILDREN WITH AUTISM: A SYSTEMATIC REVIEW - Miranda, Sthefany; Lima, João Pedro de Jesus; Nascimento, Rhuan Júnior da Silva; Rodrigues, André Gonçalves; Filho, Francisco Ronaldo Caliman; Viana, Fernando Pires; Sousa, Wanderson Sales de; Silva, Pedro Henrique de Almeida (CIPEEX, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that impairs motor, psychological, and social skills. Its prevalence is currently increasing, and physical activity is beneficial for improving these parameters in children. The objective of this study was to verify the benefits of and exercise in improving the health of children with ASD. This study is a systematic review of randomized controlled trials conducted in accordance with PRISMA guidelines. The studies included were those published in the last five years, written in English, focusing on children aged 4 to 12 years diagnosed with ASD. The databases used were PubMed, BVS, and SciELO. Of the 211 studies found, only 9 met the selection criteria. The Physiotherapy Evidence Database (PEDro) scale was used to assess the methodological quality of the studies. The results of the selected trials indicated that physical exercise improves sleep quality and physical aspects in children with ASD. It is concluded that children with ASD should perform physical exercises to improve sleep and physical aspects. Thus, it contributes to greater autonomy and independence, which is associated with a more favorable quality of life.